Rethinking the "mirroring" hypothesis: implications for technological modularity, tacit coordination, and radical innovation - Hao, Bin; Feng, Yanan; Frigant, Vincent (Wiley, 2015)
Studies of the 'mirroring' hypothesis have demonstrated the relationships between technological modularity and explicit coordination, yet little is known about the 'mirroring' relationship between technological modularity and tacit coordination, and how the 'mirroring' relationship may affect radical innovation. This paper contributes to the 'mirroring' hypothesis by identifying the interaction mechanisms embedded in and surrounded over the mirroring relationships. Using survey data of 121 high-tech firms in China, our study indicates that technological modularity enhances interfirm tacit coordination between module-makers ('mirroring' hypothesis), and will also positively influence radical innovation ('outcome' hypothesis). Moreover, tacit coordination negatively moderates the impact of technological modularity on radical innovation ('interaction' hypothesis), indicating that the 'mirroring' relationship may offset the benefit obtained from modularization. It also suggests that, in a high-technology industry in underdeveloped areas, tacit coordination could lead to exposure of hidden knowledge, thus lowering module-makers' motivation for technology breakthrough.